Improvement the germination characteristics in aged seeds of Hordeum vulgare plants by some invigoration solutions - buhwish, Rabha (Scientific Journal for Faculty of Science-Sirte University, 2023)
Seeds viability and seed vigour decline during storage, The aim of this research was the improvement of seed quality by treatment with KNO3and ZnSO4 of Hordeum vulgare L. plants aged seeds.Experiment was on barley seeds storage for different periods of (1year and 4 years) in open storage type and treatment these by using seeds invigoration solutions , 3% zinc sulfate (ZnSO4),and 3% potassium nitrate (KNO3) in addition to non primed seed (control) to know their effect on viability and vigour of Seeds and determine the best one on them. The results showed that growth parametres, total available carbohydrate (TAC) content and starch (St) contents decrease under long storage,while total soluble sugars (TSS) increased. While at treatment by ZnSO4 and KNO3 there wasan increase in total germination , mean germination time, radical and plumule lengths, seedling fresh and dry weight, and vigour index , also increasing in TSS, St, and TAC contents. However, the treatment with KNO3 was the best compare with treatment by ZnSO4. Conclusions: It can be concluded from this study that using invigoration solutions led to improve germination and vigour of barley seeds for all the seed storage.